EFFECT OF ADDITIONAL Ni METAL DOPANTS ON OPTICAL ABSORPTION PROPERTIES AND CRYSTAL STRUCTURE OF ZnO PHOTOCATALYST MATERIALS - Istiroyah Istiroyah; H. Harsono; M. Nurhuda; T.S. Utami; A.A. Dardiri; Y. Engge; F. Maulana (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
The addition of Ni metal dopants to the ZnO photocatalyst material has been carried out using the immersion method followed by sonication. The variables observed included variations in the concentration of addition of Ni and sonication time. The results of the optical absorption analysis from the uv-vis test showed that the optimum condition was reached at a concentration of 25% Ni and a sonication time of 30 minutes. The optical absorption peak has shifted towards the wavelength of visible light and new absorption peaks have been observed in the wavelength range of 425-450 nm and 650-750 nm. The energy band gap also decreased from 3.22 eV to 3.09 eV. While the crystal size analysis of the XRD diffraction pattern showed a decrease in the crystal size at 25%Ni from 105.012nm to 78.545nm.